Implementasi Prinsip Tanggung Jawab Negara dalam Mitigasi Perubahan Iklim Berdasarkan Paris Agreement - L, Lazarus (Media Hukum Indonesia (MHI), 2026)
Climate change has become a global challenge that requires a collective commitment from all countries in the world. The Paris Agreement serves as an international legal framework that regulates the responsibilities of each state in climate change mitigation efforts through the principle of common but differentiated responsibilities and respective capabilities. Indonesia, as a developing country that has ratified this agreement through Law Number 16 of 2016, has a legal obligation to reduce greenhouse gas emissions in accordance with its capabilities. This study examines how the principle of state responsibility in climate change mitigation is implemented in Indonesia based on the Paris Agreement, as well as the obstacles encountered in its implementation. The research method employed is normative juridical, using statutory and conceptual approaches. The findings indicate that Indonesia has undertaken various implementation efforts through its Nationally Determined Contribution (NDC). However, challenges in financing, technology, and cross-sectoral coordination continue to hinder the achievement of emission reduction targets..